2014
DOI: 10.1155/2014/828492
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Dielectric Studies of Monoclinic Nanosized Zirconia

Abstract: Zirconium dioxide is a prospective high-κmaterial that can replace silicon dioxide. Zirconium dioxide nanoparticle has been synthesized using sol-gel process at room temperature. The structural and morphological characterization of the nanoscaled zirconium dioxide is done using FTIR, SEM, X-ray diffraction, and TEM. The particle size of the synthesized ZrO2is observed in the range of 50–80 nm with an average crystallite size of 2–10 nm. The results are compared with commercial coarse zirconia which showed a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…However, surfactants facilitate an easier method to control morphology, size, and size distribution. As example, different zirconia properties were achieved with the same precursor as reported by Nesamani et al and Siddiqui et al These two experiments confirmed that properties of zirconia were highly influenced by the surfactant source.…”
Section: Synthesis Of Zirconia and Zirconia Nanocompositessupporting
confidence: 74%
“…However, surfactants facilitate an easier method to control morphology, size, and size distribution. As example, different zirconia properties were achieved with the same precursor as reported by Nesamani et al and Siddiqui et al These two experiments confirmed that properties of zirconia were highly influenced by the surfactant source.…”
Section: Synthesis Of Zirconia and Zirconia Nanocompositessupporting
confidence: 74%
“…Moreover, the dielectric breakdown strength of P(VDF-TrFE-CTFE) doped with 10 wt.% DEHP decreased from 269 V/µm for a neat terpolymer to 207 V/µm. The dielectric strength in this case is significantly better compared to other methods such as adding organo-metallic compounds to P(VDF-TrFE-CFE) proposed by Zhang et al which decreased the dielectric strength from 200V/µm of the neat terpolymer to 13 V/µm.8,30,66,68…”
mentioning
confidence: 71%
“…Chapter 3 30 7.40E-05 31 5.89 TiO2 48 32 2.58E-07 33 3.90 BaTiO3 1200 34 1.00E-11 35,36 5.85 Ag N.A. 6.11E7 37 10.50 37 A cuboid of dimension 0.5 x 0.5 x 1.0 µm (W x L x H) is modelled in the simulation package and the material properties of the EAP are input for calculation.…”
Section: Experimental Methodologymentioning
confidence: 99%